(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the present study was to describe the case of a 73-year-old elderly woman patient with severe sleep bruxism and social anxiety treated with cognitive-behavioral therapy combined with mindfulness and social skills training. A single case was assessed in pre- and post-intervention and 6-month follow-up. The treatment was carried out for 21 sessions of 60 minutes of psychotherapy in a school clinic. The following measures were used: Questionnaire for Detecting Sleep Bruxism (QDSB), the Pittsburgh Sleep Quality Index (PSQI), the Perceived Stress Scale (PSS-14), the Beck Anxiety Inventory (BAI), the Brunel Mood Scale (BRUMS), and daily measures. Results indicated improvement for all variables: reduction in sleep bruxism episodes, anxiety, and stress levels and improvement in humor level. In summary, these significant changes in patient’ well-being and quality of life were evident. Therefore, cognitive-behavioral therapies such as psychotherapy, physical exercise, and lifestyle changes, which are aimed at stress and anxiety reduction, may be auxiliary in the treatment of sleep bruxism.